Sex and the radical imagination in the Berkeley Barb and the San Francisco Oracle. (29th November 2018) - McEneaney, Sinead
Abstract : This paper looks specifically at two influential newspapers of the American underground press during the 1960s. Using the Berkeley Barb and the San Francisco Oracle, the paper proposes two arguments: first, that the inability of the countercultural press to envisage real alternatives to sexuality and sex roles stifled any wider attempt within the countercultural movement to address concerns around gender relations; and second, the limitation of the 'radical' imagination invites us to question the extent to which these papers can be considered radical or countercultural. The reinforcement of heterosexism, especially the primacy of the male gaze, gave little space for any radical challenge to gender norms.